Compassion fatigue and compassion satisfaction among Romanian emergency medicine personnel - Hăisan, Anca; Hogaș, Simona; Măirean, Cornelia; Punei, Mirabela-Olivia; Volovăț, Simona Ruxandra; Hogaș, Mihai; Kantor, Cristina; Cimpoeșu, Diana (Frontiers in Medicine, 2023)
Background: Contemporary scientific literature has emphasized two specific aspects of healthcare professionals: compassion satisfaction and compassion fatigue. In the context of the COVID-19 pandemic, which has placed significant strain on health systems and healthcare workers, the Russian-Ukrainian crisis appears to have a magnifying effect, particularly on mental health.The aim of the present study was to investigate the relationship between threat perception, daily worries, and professional quality of life in a sample of Emergency Medicine Personnel during two major events mentioned above. The sample included 372 participants (56.7% nurses and 43.3% physicians) from emergency units in five county hospitals in the Eastern region of Romania.The study revealed that threats related to the pandemic were positively linked to secondary traumatic stress, and daily worries were positively linked to both secondary traumatic stress and burnout. Threats generated by the war did not manifest a direct relation with any of the indicators of professional quality of life, but daily worries generated by war positively predicted both secondary traumatic stress and burnout.Conclusions: Both the pandemic, which involved cumulative exposure, and the war, which involved a lower and more distant level of exposure, had the potential to generate worries and predict a low quality of life. However, our results did not reveal any association between threats, worries, and compassion satisfaction. As a result, this positive indicator of quality of life remained stable despite the presence of threats and worries.